Hubungan Kepercayaan Pasien, Digitalisasi Layanan, Dan Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Inap Kelas 2 Dan 3 Di Rsud Karawang - jatnika adhi; Novie Mauliku; Ayu Laili Rahmiyati (LPPM ITEKES Mahardika, 2026)
Patient satisfaction is a key indicator of hospital service quality, particularly in Class 2 and 3 inpatient services that serve people from various socio-economic backgrounds. As a regional referral hospital, Karawang Regional General Hospital (RSUD Karawang) continues to strive to improve service quality amidst the high public demand for fast, safe, and quality health services. This study aims to analyze the influence of patient trust, service digitalization, and service quality on the satisfaction of Class 2 and Class 3 inpatients at Karawang Regional General Hospital. This quantitative study with a cross-sectional approach involved 123 patients selected based on inclusion criteria. Data were collected through a structured questionnaire and analyzed using univariate, bivariate, and multivariate analysis with logistic regression. The results showed that patient trust had a significant relationship with patient satisfaction (Pvalue = 0.037). In contrast, service digitalization did not show a significant relationship (Pvalue = 0.087). Service quality was shown to be significantly related and the most dominant factor influencing patient satisfaction (Pvalue = 0.001). These findings indicate that patient satisfaction is more influenced by directly perceived aspects, such as staff attitude, responsiveness, and clarity of information, than by digital systems. Therefore, ongoing efforts are needed to improve service quality, strengthen communication, and develop more user-friendly digitalization.